Think Globally, Act Locally: The Contextualization of Gentle-Parenting through the Sundanese Values of Asih, Asah, and Asuh - Febrianti, Adinda Aulya; Nurbayani, Siti; Wilodati, Wilodati (FKIP Universitas Lampung, 2025)
Think Globally, Act Locally: The Contextualization of Gentle-Parenting through the Sundanese Values of Asih, Asah, and Asuh. Objective: In response to the global shift towards more empathetic parenting practices as a counter-narrative to traditional parenting, which often employs a directive approach, this study addresses the need for culturally relevant child-parenting models. It aims to explore the lived parenting experiences of contemporary Sundanese families and, subsequently, to identify how the local philosophical values of asih (nurturing affection), asah (honing potential), and asuh (protective guidance) serve as an indigenous framework to contextualize and reinterpret the principles of gentle-parenting in their daily lives. Methods: This study employed a qualitative, exploratory approach using a phenomenological method. The data were collected through in-depth, semi-structured interviews with a small, purposively selected sample of three Sundanese families who practice an emphatic parenting approach in the Greater Bandung area. Thematic analysis was used to identify patterns and convergences between lived experiences and theoretical concepts. Findings: The findings reveal a significant convergence between the two paradigms. The parenting practices of the participating families, although not explicitly labeled as such, inherently embody core principles of gentle parenting. The value of asih is manifested as the foundational practice of building secure emotional connections and validating children's feelings. The value of asah was realized through dialogical practices that stimulate a child's critical reasoning and skills. Finally, asuh was implemented as a framework of protective nurturing, characterized by consistent role-modeling and the setting of rational, rather than punitive, limits. Conclusion: The Sundanese local wisdom of asih, asah, and asuh is not merely compatible with gentle parenting but functions as a robust, pre-existing cultural framework to